The impact of migration and antimicrobial resistance on the transmission dynamics of typhoid fever in Kathmandu, Nepal: A mathematical modelling study. - Saad, N; Bowles, C; Grenfell, B; Basnyat, B; Arjyal, A; Dongol, S; Karkey, A; Baker, S; Pitzer, V (Public Library of Science, 2017)
Background A substantial proportion of the global burden of typhoid fever occurs in South Asia. Kathmandu, Nepal experienced a substantial increase in the number of typhoid fever cases (caused by Salmonella Typhi) between 2000 and 2003, which subsequently declined but to a higher endemic level than in 2000. This epidemic of S. Typhi coincided with an increase in organisms with reduced susceptibility against fluoroquinolones, the emergence of S. Typhi H58, and an increase in the migratory population in Kathmandu. Methods We devised a mathematical model to investigate the potential epidemic drivers of typhoid in Kathmandu and fit this model to weekly data of S. Typhi cases between April 1997 and June 2011 and the age distribution of S. Typhi cases. We used this model to determine if the typhoid epidemic in Kathmandu was driven by heightened migration, the emergence of organisms with reduced susceptibility against fluoroquinolones or a combination of these factors. Results Models allowing for the migration of susceptible individuals into Kathmandu alone or in combination with the emergence of S. Typhi with reduced susceptibility against fluoroquinolones provided a good fit for the data. The emergence of organisms with reduced susceptibility against fluoroquinolones organisms alone, either through an increase in disease duration or increased transmission, did not fully explain the pattern of S. Typhi infections. Conclusions Our analysis is consistent with the hypothesis that the increase in typhoid fever in Kathmandu was associated with the migration of susceptible individuals into the city and aided by the emergence of reduced susceptibility against fluoroquinolones. These data support identifying and targeting migrant populations with typhoid immunization programmes to prevent transmission and disease.